Small Cell Lung Cancer Patient with Profound Hyponatremia and Acute Neurological Symptoms: An Effective Treatment with Fludrocortisone - Jana Jaal; Tõnu Jõgi; Alan Altraja (Case Reports in Oncological Medicine)
Hyponatremia is a frequent electrolyte abnormality in patients with small cell lung cancer (SCLC). Being usually asymptomatic, hyponatremia may cause symptoms like nausea, fatigue, disorientation, headache, muscle cramps, or even seizures, particularly if severe and rapid decrease of serum sodium levels occurs. Here we report a case of SCLC patient with severe hyponatremia and acute neurological symptoms that developed 2 days after the first course of second-line chemotherapy, most probably due to the release of antidiuretic hormone (ADH, also known as arginine vasopressin) during lysis of the tumour cells. Initial treatment consisted of continuous administration of hypertonic saline that resulted in improvement of patient’s neurological status. However, to obtain a persistent increase in serum sodium level, pharmacological intervention with oral fludrocortisone 0.1 mg twice daily was needed. We can therefore conclude that mineralocorticoids may be used to correct hyponatremia in SCLC patients when appropriate.